DESAIN DIDAKTIS BERPIKIR KREATIF MATEMATIS PADA MATERI BANGUN RUANG SISI DATAR BERBANTUAN GEOGEBRA - Nurcahyo Ade Prasetyo, - (2019)
Nurcahyo Ade Prasetyo (1504822). Didactical Design for Mathematical Creative Thinking on The Topic of Solid Geometry Through Geogebra. The existence of less meaningful learning makes the learning obstacles and the difficult to improve their high order thinking skills especially creative thinking skill. This research aims to make didactic design that will minimize the learning obstacles and practice their ability of thinking creatively. This didactic design consist of 2 lesson designs that implemented by geogebra as tools to find mathematical concepts also for demonstration and visualization. Moreover, in this didactic design, there are exercise and quiz based on indicator of creative thinking. This research was conducted for 8th grader (34 students) who never learn surface area and volume of pyramid. The research method used is a qualitative research method with data collection techniques by means of triangulation that combining observational data, interviews, and documentation. Based on the results of the research, this didactic design can minimize learning obstacles and train students to think creatively so that they can be used as alternative teaching materials in learning surface area and volume of pyramid. Key Words : Didactical Design, Mathematical Creative Thinking, Pyramid, Geogebra